Secrets from friends and parents: Longitudinal links with depression and antisocial behavior. Issue 4 (7th June 2013) - Laird, Robert D.; Bridges, Brittanee J.; Marsee, Monica A.
ABSTRACT: Keeping secrets from parents is associated with depression and antisocial behavior. The current study tested whether keeping secrets from best friends is similarly linked to maladjustment, and whether associations between secrecy and maladjustment are moderated by the quality of the friendship. Adolescents ( N  = 181; 51% female, 48% white, non‐Hispanic, 45% African American) reported their secrecy from parents and best friends, the quality of their parent–adolescent relationships and best friendships, and their depression and antisocial behavior at ages 12 and 13. Keeping more secrets from best friends was associated with more depression, but not with more antisocial behavior, when controlling for earlier adjustment, secrecy from parents, and the quality of the friendship. For girls associations between maladjustment and secrecy were conditioned by the quality of the relationships and whether secrets were kept from parents and friends. Discussion argues for expanding the study of secrecy in adolescence beyond the parent–child dyad.